Transformações nos perfis dos reitores e presidentes de instituições de ensino superior da região sudeste brasileira - Freitas, Rafael de (Universidade Federal de São Carlos, 2021)
This paper investigates the transformations in the last 30 years in the Rectors' and Presidents' profiles of higher education institutions in the southeastern region of Brazil based on the analysis of their trajectories. It uses as theoretical reference the contributions of sociologist Pierre Bourdieu and his studies on the university field in order to identify possible changes in the forms of capital accumulation in these institutions. For this study, a prosopographical research was carried out based on data obtained from the Lattes curricula and, for data analysis, the technique of multiple correspondence analysis - MCA - was applied. A change was observed especially in the rectors of federal universities, who proceeded to have a trajectory of greater accumulation of scientific capital and university management.
Changes in the profiles of rectors and presidents of higher education institutions in the southeast of Brazil
Keywords: Campo Universitário; Elites dirigentes; Reitor; University Field; Ruling elites; Rector; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE SISTEMAS EDUCACIONAIS; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE UNIDADES EDUCATIVAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA